2013
DOI: 10.1890/es12-00339.1
|View full text |Cite
|
Sign up to set email alerts
|

Population origin and genome size do not impactPanicum virgatum(switchgrass) responses to variable precipitation

Abstract: Population‐level adaptation to broad‐scale regional climates or within‐population variation in genome size of the genetically and phenotypically diverse C4 grass, Panicum virgatum (switchgrass), may influence the responses of this species to future precipitation variability associated with climate change. Therefore, we investigated P. virgatum responses to water variability between natural populations collected across a latitudinal gradient and among individuals spanning a range of genomes sizes within these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Physiology is well known to change throughout the development of a plant, and thus mistiming in phenology can have consequences for how plants respond physiologically to major environmental stresses, such as drought and freezing temperatures (Araus et al 2002;McKay et al 2003;Fowler and Limin 2004;Bigras and Bertrand 2006;Roux et al 2006;Lovell et al 2013;Savage and Cavender-Bares 2013). Recent studies suggest a possible association of leaf-level physiological traits with latitude of origin in P. virgatum (Hartman et al 2012;Aspinwall et al 2013), but more studies are needed to clarify the strength of these relationships (O'Keefe et al 2013).…”
Section: Variation Associated With Large-scale Environmental Gradientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physiology is well known to change throughout the development of a plant, and thus mistiming in phenology can have consequences for how plants respond physiologically to major environmental stresses, such as drought and freezing temperatures (Araus et al 2002;McKay et al 2003;Fowler and Limin 2004;Bigras and Bertrand 2006;Roux et al 2006;Lovell et al 2013;Savage and Cavender-Bares 2013). Recent studies suggest a possible association of leaf-level physiological traits with latitude of origin in P. virgatum (Hartman et al 2012;Aspinwall et al 2013), but more studies are needed to clarify the strength of these relationships (O'Keefe et al 2013).…”
Section: Variation Associated With Large-scale Environmental Gradientsmentioning
confidence: 99%
“…Both ecotype status (upland vs. lowland) and latitude have been established as important sources of variation responsible for adaptation in P. virgatum (Porter 1966;McMillan 1969b;Sanderson et al 1999b;Casler et al 2004Casler et al , 2007Kiniry et al 2013). The effect of ploidy (tetraploid vs. octoploid) on adaptive trait divergence has also been evaluated in many studies but has rarely been found to have a major effect on phenotype or fitness in the field (Nielsen 1947;McMillan and Weiler 1959;Warner et al 1987;Wullschleger et al 1996;O'Keefe et al 2013). Further, ploidy is often confounded with ecotype (Warner et al 1987;Wullschleger et al 1996) or latitude of origin (Nielsen 1947;McMillan and Weiler 1959;O'Keefe et al 2013), making it difficult to determine the effects these three major sources of variation have on adaptation.…”
Section: Future Studies On Genetic Mechanisms Of Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Different switchgrass varieties show different leaf photosynthetic rates, ranging from 25.4 to 35.4 μmol CO 2 m -2 s -1 [ 33 ]. Compared to other crop types, the effects of climate change, such as water stresses on switchgrass, have not been well investigated [ 21 , 34 , 35 ]. Some studies compared differences in annual precipitation and temperature and found that inter-annual precipitation influences soil water availability and then the physiology of switchgrass [ 21 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The soil water stress significantly reduced switchgrass aboveground biomass, establishment rates of stands, and physiological responses [ 36 39 ]. But few experimental studies have been conducted to investigate the responses of switchgrass physiology and growth to climate changes [ 21 , 35 , 39 ].…”
Section: Introductionmentioning
confidence: 99%